THE HISTOLOGICAL AND PHYSIOLOGICAL ALTERATIONS IN GILLS AND ERYTHROCYTES OF C YPRIN US CARPIO AND LIZA AB U AS BIOMARKER TO FRESHWATER POLLUTION - Al-Ali M. F. M (Basrah Journal of Veterinary Research)
As a component of a large research programme to evaluate the effects. of contaminants on ﬁsh health in the ﬁelds , histopathological studies have been conducted to help establish meat of causal relationships between contaminants exposure and various biological responses and use of those responses as biomarker to aquatic pollution . Two ﬁsh species C. carpio and L. abu were sampled from four sites near of industrialize and human pollution areas from _ Shatt Al-Arab River ,while the ﬁfth place was considered as control because it's far located from direct pollution sources . Some of histological and physiological alterations were examined in both gills and blood . The alterations were signiﬁcantly higher in ﬁsh collected from two places ( 1 & 2 ) compare with other sites , histological was represented by hyperplasia , hypertrophy , bleeding , inﬂammations , edema , necrosis , epithelial separation and clubbing shaped , while , physiological was represented‘ by decrease of Na+ , K+ , Ca” concentrations , Chloride cells number and increase of respiratory diffusion distance , in addition to , increase of micronuclear of red blood cells . all ﬁsh in ﬁfth place didn't showed any histological and physiological responses and retained their rates of the normal level compares with other places